Methylene blue adsorption mechanism onto palm kernel shell-derived activated carbon : From particle diffusion to site adsorption - Khairul Anwar, Mohamad Said; Mohamed Afizal, Mohamed Amin; Ibrahim, Yakub; Md Rezaur, Rahman; Ahmad Beng Hong, Kueh; Sinin, Hamdan; Mohammed, M. Rahman (NC State University, 2023)
The mechanism of methylene blue adsorption was investigated for palm kernel shell-derived activated carbon from the bulk solution to active sites. For different initial dye concentrations, 100 ppm methylene blue led to approximately 10 mg/g adsorption capacity while experiencing a decreasing trend at lower initial dye concentrations as follows: 50 ppm (approximately 5 mg/g) > 20 ppm (approximately 2 mg/g) > 5 ppm (approximately 0.5 mg/g). Based on the Boyd external diffusion model, the mechanism of methylene blue adsorption started with its diffusion from the bulk solution via the bounding film encapsulating the activated carbon. The adsorbed species occupied more than one class of active site with an adsorption rate of 0.54 mg/g.min, while the adsorption capacity accounted for 14.7 mg/g. The information about methylene blue offers useful insights into describing the steps of dye adsorption onto palm kernel shell-activated carbon.